2020
DOI: 10.1093/sleep/zsaa056.893
|View full text |Cite
|
Sign up to set email alerts
|

0897 Sleep Disordered Breathing In Pediatric Patients With Turner Syndrome

Abstract: Introduction Turner syndrome (TS) is a common genetic disorder that affects phenotypic females with partial or complete absence of one X chromosome. It typically presents with characteristic facial appearance, neck webbing, lymphedema, linear growth failure, and ovarian insufficiency. TS is also associated with other disorders, though sleep related disorders are not commonly reported. We present a case series of pediatric patients diagnosed with TS and assess their risk for sleep disordered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The first case report describing an association between OSA and TS discusses a 32‐year‐old nonobese woman with TS, a narrow upper airway and brachycephaly, whose OSA resolved after maxillomandibular advancement osteotomy 6 . Subsequently, small case series have described an association between OSA and TS 7,8 . A large retrospective review of patients aged 2 to 26 years reported a 9% prevalence of sleep apnea in TS 9 ; however, this study did not provide diagnostic criteria for sleep apnea, polysomnogram (PSG) data, age of diagnosis, or risk factors.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The first case report describing an association between OSA and TS discusses a 32‐year‐old nonobese woman with TS, a narrow upper airway and brachycephaly, whose OSA resolved after maxillomandibular advancement osteotomy 6 . Subsequently, small case series have described an association between OSA and TS 7,8 . A large retrospective review of patients aged 2 to 26 years reported a 9% prevalence of sleep apnea in TS 9 ; however, this study did not provide diagnostic criteria for sleep apnea, polysomnogram (PSG) data, age of diagnosis, or risk factors.…”
mentioning
confidence: 95%
“…6 Subsequently, small case series have described an association between OSA and TS. 7,8 A large retrospective review of patients aged 2 to 26 years reported a 9% prevalence of sleep apnea in TS 9 ; however, this study did not provide diagnostic criteria for sleep apnea, polysomnogram (PSG) data, age of diagnosis, or risk factors.…”
mentioning
confidence: 95%